Pengaruh Implementasi Green Accounting, Material Flow Cost Accounting dan Environmental Performance terhadap Sustainable Development - Kiuk, Maria Felinsia Laga; Yohana Febiani Angi; Novi Theresia Kiak (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study was conducted with the aim of examining the effect of green accounting implementation, material flow cost accounting and environmental performance on sustainable development. The population of this study were 26 palm oil companies listed on the IDX for the period 2020-2023 and the total sample collected from the purposive sampling method was 15 companies with 60 observation data. The data used is secondary data with the analysis carried out including descriptive statistics, panel data regression and hypothesis testing in the form of t test, F test, and coefficient of determination analyzed using the eviews version 12 application. The results of the research conducted explain that green accounting and environmental performance partially have no effect on sustainable development, while material flow cost accounting partially affects sustainable development. Meanwhile, if the F test is carried out, then green accounting, material flow cost accounting and environmental performance simultaneously affect sustainable development.